Dissecting the proteome of lipoproteins: New biomarkers for cardiovascular diseases?. Issue 7 (June 2015) - von Zychlinski, Anne; Kleffmann, Torsten
Graphical abstract: Highlights: Lipoproteins are key players in the development of cardiovascular disease. Shotgun proteomics broadened our view of a complex picture of lipoprotein functions. Besides established CVD markers novel lipoprotein-related markers are still missing. Targeted approached such as MRM and DIA-MS show great promise for the identification and evaluation of new candidate markers. Abstract: Proteomics has proven to be a powerful tool for the characterization of lipoproteins and has provided important insights into the biochemistry and pathophysiology of various lipoprotein classes. It has significantly contributed to the way we now see lipoproteins as complex particles not only involved in lipid transport and exchange, but also in processes such as immune response, inflammation and wound healing. Ongoing proteomics research is focussing on the identification of new candidate markers for cardiovascular disease, the leading cause of death worldwide. The ratio between good cholesterol (high density lipoprotein) and bad cholesterol (low density lipoprotein) is routinely used to estimate an individual's risk for developing premature coronary heart disease. While statin therapy has proven effects in reducing cardiovascular events, other therapies such as resins, fibrates and niacin have failed to substantially reduce cardiovascular risk. Thus new targets and candidate biomarkers for risk assessment and for the development of alternative drugs and treatments of disease are needed. Here we review the recent findings in lipoprotein proteomics with the main emphasis on studies that differentially displayed various states of diseases and on new targeted, high throughput strategies with the capability to translate discovery findings into the clinical context of large cohort analyzes.